2001
DOI: 10.1081/pb-100107485
|View full text |Cite
|
Sign up to set email alerts
|

SIMPLIFIED METHOD FOR THE DETECTION OF Apo(a) ISOFORMS

Abstract: Apolipoprotein a, is a high molecular weight glycoproteic component of Lp(a), a molecule associated with coronary arterial disease. Apo(a) exhibits considerable size heterogeneity due to variable repetitions of the carbohydrate-containing structural unit, termed kringle. There are five different kringle forms and 10 different kringle 4 types. Apo(a) polymorphism and molecular weight depend on the number of copies of kringle 4 type 2. In this paper we describe a modified 3.75% and 6% discontinuous polyacrylamid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…14 -16 Recently, a large Mendelian randomization study reported association between low KIV-2 copy number and myocardial infarction in a sample of European Caucasians but did not include single-nucleotide polymorphism (SNP) genotypes. 17 To date, KIV-2 copy number generally has been identified either at the biochemical level by examining the protein size using electrophoresis and immunoblotting 18,19 or at the genomic level using pulse-field gel electrophoresis with Southern blotting of unamplified genomic DNA. 19 Because of the requirement of either large amounts of fresh plasma or genomic DNA, respectively, for these methods, candidategene and genome-wide association studies of Lp(a) concentration have not included the apo(a) KIV-2 copy number as a covariate or independent variable, nor has there been any opportunity to study association or linkage disequilibrium between LPA SNPs and KIV-2 copy number.…”
Section: Clinical Perspective On P 46mentioning
confidence: 99%
“…14 -16 Recently, a large Mendelian randomization study reported association between low KIV-2 copy number and myocardial infarction in a sample of European Caucasians but did not include single-nucleotide polymorphism (SNP) genotypes. 17 To date, KIV-2 copy number generally has been identified either at the biochemical level by examining the protein size using electrophoresis and immunoblotting 18,19 or at the genomic level using pulse-field gel electrophoresis with Southern blotting of unamplified genomic DNA. 19 Because of the requirement of either large amounts of fresh plasma or genomic DNA, respectively, for these methods, candidategene and genome-wide association studies of Lp(a) concentration have not included the apo(a) KIV-2 copy number as a covariate or independent variable, nor has there been any opportunity to study association or linkage disequilibrium between LPA SNPs and KIV-2 copy number.…”
Section: Clinical Perspective On P 46mentioning
confidence: 99%